Separation and Determination of Free Fatty Acids in Corn Oil and Palm Oil by Liquid-Liquid Extraction and Acidi-Alkalimetric Titration - Rusdi, Hanumi Oktiyani; Kusumaningrum, Irma Kartika; Nareswari, Tsalis Jauza; Fauziah, Putri Nanda; Maharani, Richa Nan; Natasya, Shella (Walisongo Journal of Chemistry, 2024)
Free Fatty Acids (FFA), which include unsaturated fatty acids like oleic and linoleic acid and saturated fatty acids like palmitic and stearic, are present in most oil compositions. The various negative impacts of FFA require these compounds to be eliminated.  This research aims to separate FFA using Liquid-Liquid Extraction (LLE) and determine the levels of FFA using acid-alkalimetric titration in corn oil and palm oil. FFA extraction was carried out for 4 minutes with a solvent ratio of 9,5 ml diethyl ether + 40 ml ethanol + 0,5 ml water. By adding 1M Na2SO4, re-extraction was carried out for 3 minutes. The results obtained were 0.95% FFA levels in corn oil and 1.26% FFA levels in palm oil. FFA levels of both oils are still below the SNI FFA percentage of 3%; besides that, it is found that the FFA levels in palm oil are higher than in corn oil